Bioart and the vitality of media - Mitchell, Robert, 1969- (In vivo (Seattle, Wash.), 2010)
"All rights reserved. No part of this publication may be reproduced or transmitted in any form or by any means, electronic or mechanical, including photocopy, recording, or any information storage or retrieval system, without permission in writing from the publisher."--Jacket